2018
DOI: 10.1177/0973801018800087
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impact of Natural Disasters: An Empirical Re-examination

Abstract: Natural disasters cause serious economic and human losses. Yet there remains ambiguity in the existing literature with regard to their impact on the economy at large. This study re-examines the relationship between natural disasters and economic growth. It aims to contribute to a fairly limited literature on the economy-wide and sector-specific consequences of natural disasters in the short-to-medium term (up to 5 years). Further, it examines whether the disaster impacts are dependent on a country’s level of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 51 publications
2
83
0
2
Order By: Relevance
“…Since the geological events, both created by the internal dynamics of the earth and induced by man, occur within certain rules, it will be possible to deal with events from both origins by applying scientific rules. Panwar and Sen (2019) investigated the effects of four types of natural disasters, namely flood, drought, storm and earthquake, on growth, and their macroeconomic consequences, using panel data from 102 countries in the 1981-2015 period. Researchers have found that natural disasters have different effects on macroeconomics and vary between economic sectors according to disaster types and intensities.…”
Section: Discussionmentioning
confidence: 99%
“…Since the geological events, both created by the internal dynamics of the earth and induced by man, occur within certain rules, it will be possible to deal with events from both origins by applying scientific rules. Panwar and Sen (2019) investigated the effects of four types of natural disasters, namely flood, drought, storm and earthquake, on growth, and their macroeconomic consequences, using panel data from 102 countries in the 1981-2015 period. Researchers have found that natural disasters have different effects on macroeconomics and vary between economic sectors according to disaster types and intensities.…”
Section: Discussionmentioning
confidence: 99%
“…In databases with records of floods, it is uncommon for criteria on event inclusion to require a declaration of flood subtype [47][48][49]. Even in databases that include subtypes, protocols are unlikely to exist for disaggregating, tagging [50,51] or for attributing magnitude of direct and indirect impacts [52]. However, in a database including only primary flood type, there are likely to be some attributes that allow for the assignment of a subtype (such as 'flash flood') to some degree of confidence [53].…”
Section: Flash Flood As a Disaster Subtypementioning
confidence: 99%
“…Loss in labor and capital can reduce the output in several sectors like the agricultural, industrial and educational sectors, which results in minimizing the total production output. In [33], the authors present a study that summarizes the impacts of natural disasters on various economic sectors, the authors describe disaster types and their severity on the economy.…”
Section: Risks and Impactsmentioning
confidence: 99%